Bracketed radioactive seed localization vs bracketed wire‐localization in breast surgery. Issue 2 (14th July 2017) - Da Silva, Monica; Porembka, Jessica; Mokdad, Ali A.; Seiler, Stephen; Huth, James; Rivers, Aeisha; Wooldridge, Rachel; Chu, Amanda; Brown, Emily; Bao, Jean; Farr, Deborah; Hansen, Meghan; et al.
Abstract: Multiple localizers placed in a bracketed fashion facilitates excision of radiographically extensive breast lesions. In this study, bracketed radioactive seed localization (bRSL) was compared to bracketed wire localization (bWL). We hypothesized that bRSL would achieve adequate margins and decrease re‐operation rates with similar or less specimen volumes (SV) than bWL. Retrospective review identified patients who underwent bracketed breast procedures at an academic medical center. Data collected included patient demographics, tumor features, treatment variables, and surgical outcomes. Wilcoxon rank‐sum test and chi‐square test were used to compare continuous and categorical data, respectively. A multivariable logistic regression model was used to evaluate the association between re‐excision and localization technique after adjusting for clinically relevant variables. Patients who underwent bWL were 3.9 times more likely to undergo re‐excision compared to patients in bRSL group (OR=3.9, 95% CI: 2.0‐7.4). Initial and total SV did not significantly differ between the two groups ( P =.4). Patients were significantly more likely to undergo a mastectomy in the bWL group than in the bRSL group (24% vs 7%; P <.01). For patients undergoing excision of radiologically extensive breast lesions, bRSL serves as an alternative to bWL. In this retrospective study, bRSL was associated with a decreased re‐excision rate with similar SV and a lower rate of mastectomy when compared to bWL.